Analisis Penggunaan Material Batu dan Pasir dari Desa Tumbang Liting pada Campuran Hot Rolled Sheet-Base (HRS-Base) - Yubilate Lahasa; Desriantomy; Salonten (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
The need for pavement materials in Central Kalimantan is increasing along with the many developments in road infrastructure. Therefore, it is necessary to find natural resources around. Tumbang Liting Village, Katingan Hilir Sub-district, Katingan Regency, Central Kalimantan Province has abundant natural resources in the form of stone and sand resulting from local mining waste and has not been utilised properly. Stone from Tumbang Liting Village has a grain size of 5-25 mm with a surface that tends not to be angular. The research was conducted to analyse the use of stone and sand from Tumbang Liting Village as aggregates in Hot Rolled Sheet Base (HRS-Base) mixes. It is expected that the stone and sand from Tumbang Liting Village can be a solution to the need for HRS-Base pavement materials in Central Kalimantan, especially in the surrounding areas. The research was conducted in the laboratory, examining the physical properties of the aggregate to Marshall testing. The calculation results of the Marshall test obtained Optimum Asphalt Content (KAO) of 7.27%, Stability of 850.90 kg, Voids Between Aggregates (VMA) of 20.08%, Voids in the Mixture (VIM) of 4.28%, Voids Filled with Asphalt (VFA) of 78.90% and Marshall Quotient (MQ) of 265.00 kg/mm.